Characterization of ASR products in a 40-year-old highway - Locati, Francisco (2012)
The majority of crushed aggregates utilized in Argentina come from the Sierras Pampeanas of Córdoba, (Province of Córdoba). Many of the exploited lithologies are quartz-rich and have undergone deformation processes affecting their texture and producing internal microstructures. Previous studies have shown that those characteristics make rocks potentially alkali reactive. In order to compare those results with performance of aggregates in concrete structures, an important highway that links Córdoba and Villa Carlos Paz cities was studied. Preliminary results showed that this deterioration could be interpreted as a normal aging of concrete, accelerated by humidity problems and ASR development. In this work, further studies on reaction products were carried out through a stereomicroscope, a polarized light microscope, powder XRD and SEM-EDS analyses. Calcium silicates with variable contents of sodium and potassium, associated with ettringite, were identified in fissures, mortar, in the mortar-aggregate interface and filling air voids.